2022
DOI: 10.1097/prs.0000000000008991
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Letters of Recommendation in Plastic Surgery: The Impact of Gender and Race

Abstract: Background: In the last few decades, standardized letters of recommendation have seen increasing popularity among various medical specialties and have been shown to demonstrate score inflation and gender bias in some select specialties. Through analysis of standardized letter of recommendation scoring patterns, this study evaluated the impact of race and gender on performance in standardized letters of recommendation and provides suggestions for programs to optimally interpret standardized letters of recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…19,22,32 However, even the most well-written letter does not always offer insight into these qualities, and it is well known that implicit biases seep through into the content of letters of recommendation, particularly when it comes to description of these soft skills. 33 Additionally, recommendation letters written by well-connected plastic surgeons are preferentially valued, introducing another source of bias when evaluating soft skills from narrative letter content. 34,35 The results of our survey suggest that we should strive to find ways to evaluate, and more importantly, prioritize these traits in the application review process.…”
Section: How To Discern Key Attributes In the Residency Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…19,22,32 However, even the most well-written letter does not always offer insight into these qualities, and it is well known that implicit biases seep through into the content of letters of recommendation, particularly when it comes to description of these soft skills. 33 Additionally, recommendation letters written by well-connected plastic surgeons are preferentially valued, introducing another source of bias when evaluating soft skills from narrative letter content. 34,35 The results of our survey suggest that we should strive to find ways to evaluate, and more importantly, prioritize these traits in the application review process.…”
Section: How To Discern Key Attributes In the Residency Applicationmentioning
confidence: 99%
“…However, a recent publication by Reghunathan et al revealed that this question format is associated with significant score inflation and has therefore become dubiously useful in differentiating applicants. 33 Furthermore, both score inflation and biases against demographic minorities persist even in standardized letters of recommendation, with applicants of minority races receiving lower scores on average when compared with their peers. 33 To address this challenge of distinguishing candidates from a highly qualified applicant pool, holistic review is critical.…”
Section: How To Discern Key Attributes In the Residency Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Letters of recommendation can convey bias. 2 Aside from this, letters of recommendation require a degree of interpretation. A strong letter is not the longest letter, recounting the accomplishments already noted on the curriculum vitae.…”
mentioning
confidence: 99%
“…Inequities observed in the physician workforce result from multiple factors: bias from evaluators, socioeconomic disadvantage, unequal access to resources, and inadequate availability of mentorship, among others. 4,5 PREPPED is a concerted effort by several invested faculty and residents to assist a cohort of capable, highly motivated historically disadvantaged students interested in the field of plastic surgery. PREPPED represents the first national course for subinternship preparation for underrepresented students in plastic surgery (Figs.…”
mentioning
confidence: 99%